EUFEMISME KASIPALLI PADA MASYARAKAT MAKASSAR (Euphemism of Taboo in Makassarese Society) - Hastianah Hastianah (Balai Bahasa Sulawesi Selatan, 2014)
AbstractThe research intends to describe euphemism in Makassarese society. It applies descriptive method withinterviewing and listening-speaking involving technique. Furthermore, data is analyzed qualitatively usingsemantic approach. Result of research shows that euphemism forms of taboo in Makassarese society foundare (a) euphemism in farmer’s community, (b) euphemism in fishermen’s community, (c) euphemism in seller’scommunity, and (d) euphemism in circumstance’s community. Besides proposing euphemism form, the researchalso finds out euphemism classification implying taboo values like (a) taboo of being afraid, (b) taboo of beingconsidered rough, and (c) taboo of being considered impolite.